Frequency of Impaired Glucose Tolerance in Patients of Essential Hypertension in Tertiary Care Hospital, Larkana (Medical Forum Monthly, 2024)
Objective: To determine the frequency of impaired glucose tolerance in patients of essential hypertension.Study Design: Descriptive Cross sectional study.Place and Duration of Study: This study was conducted at the Medical Outpatient department of Chandka Medical College Hospital Larkana, over one year period from February 2012 to February 2013.Materials and Methods: Total 171 patients of age 40-70 years having hypertension more than 2 years were purposively selected, while Known cases of DM, secondary hypertension & metabolic syndrome were excluded. Oral glucose tolerance was performed on selected patients of essential hypertension and plasma glucose was measured 2 hours after giving 75 g of glucose to each patient. Patients with (2 hours plasma glucose) level of 140-199 mg/dl were considered impaired glucose tolerance. Frequency was calculated for gender, number & type of medication & impaired glucose tolerance. The mean & SD were calculated for age, height, weight, BMI and duration of HTN. Stratification of age, gender, BMI & duration of hypertension done while applying Chi-Square with p value <0.05 as significant.Results: One hundred and seventy one (171) patients met the inclusion criteria with mean age of 53.42 + 8.059 among those 104 were males (60.81%) while 67 were females (39.19%). Duration of hypertension ranged 3-15 years with a mean duration of 7.47 ± 3.26 years. Mean Body mass index (BMI) was 25.95 ± 4.32, minimum BMI 17.88 & maximum BMI was 39.91. Frequency of IGT was 39.2% (n=67). Mean serum glucose level at 2 hours in these patients was 159.33 ± 27.937 grams/dL. Males were more affected while age has little effect on IGT frequency. More the duration of hypertension more was the prevalence of IGT. BMI was significant effect modifier for IGT; in overweight & obese patients the frequency of IGT was much higher (40.58% in overweight & 69.23% in obese) than normal weight patients (27.78%). (p value <0.003).Conclusion: IGT is much frequent in essential hypertension. Hypertensive males, elder age, longer duration of hypertension, high BMI & use of more than one antihypertensive medicine are associated with higher rates of IGT. This study suggests that all the patients with essential hypertension should be scrutinized for blood glucose levels.